2020
DOI: 10.1111/1759-7714.13671
|View full text |Cite
|
Sign up to set email alerts
|

GPX8 promotes migration and invasion by regulating epithelial characteristics in non‐small cell lung cancer

Abstract: Background Non‐small cell lung cancer (NSCLC) is the most common cause of cancer‐related death worldwide. The family of glutathione peroxidase (GPX), an important antioxidant enzyme in human tissues, has been discovered to play a key role in the development of cancers. GPX8 is the most promising molecule of the family in a therapeutic strategy against a variety of cancers. The main purpose of this study was to examine and analyze the function and clinical value of GPX8 in NSCLC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…PLEK2 is also involved in cancer invasion and metastasis in gallbladder cancer [26], pancreatic cancer [27], non-small cell lung cancer [28]. Consistent with our ndings, GPX8 is also identi ed as a prognostic biomarker of gastric cancer [29], and is essential for tumor aggressiveness in breast cancer [30], non-small cell lung cancer [31], and gastric cancer [32]. FSCN1 was implicated in nasopharyngeal carcinoma [33] and non-small cell lung cancer [34].…”
Section: Discussionsupporting
confidence: 83%
“…PLEK2 is also involved in cancer invasion and metastasis in gallbladder cancer [26], pancreatic cancer [27], non-small cell lung cancer [28]. Consistent with our ndings, GPX8 is also identi ed as a prognostic biomarker of gastric cancer [29], and is essential for tumor aggressiveness in breast cancer [30], non-small cell lung cancer [31], and gastric cancer [32]. FSCN1 was implicated in nasopharyngeal carcinoma [33] and non-small cell lung cancer [34].…”
Section: Discussionsupporting
confidence: 83%
“…GPx8 is a membrane protein located on the endoplasmic reticulum (ER) and is a molecular gatekeeper that plays a vital role in regulating H 2 O 2 , where the knockdown of GPx8 in HEK-293 cells encourages ER stress and decreased cellular viability [ 37 ]. Zhang et al showed that GPx8 promotes migration and invasion, where high expression of GPx8 in lung cancer was correlated with a worse clinical outcome and prognosis [ 38 ]. Additionally, a recent study demonstrated GPx8 as a critical player in a metabolic-inflammatory pathway that acts as a robust regulator of cancer cell aggressiveness [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione peroxidase 8 (GPX8), another type II transmembrane protein, also localized at MAMs, has a role in the modulation of Ca 2+ dynamics [87]. In particular, GPX8 overexpression causes a decreased ER calcium coupled with a reduction of the ER-mitochondria calcium flux [88]. ER chaperones and folding assistants modulate cell metabolism and survival by controlling ER-mitochondria calcium flux.…”
Section: Regulation Of Oxidative Stress Under Normal Conditionsmentioning
confidence: 99%